Outcomes of patients with spontaneous coronary artery dissection. Issue 2 (24th August 2016) - McGrath-Cadell, Lucy; McKenzie, Pamela; Emmanuel, Sam; Muller, David W M; Graham, Robert M; Holloway, Cameron J
Abstract : Background: Spontaneous coronary artery dissection (SCAD) is an uncommon but serious condition presenting as an acute coronary syndrome (ACS) or cardiac arrest. The pathophysiology and outcomes are poorly understood. We investigated the characteristics and outcomes of patients presenting with SCAD. Methods: In a retrospective study of a large cohort of patients with SCAD, data were collected regarding clinical presentation, patient characteristics, vascular screening, coronary artery involvement and clinical outcomes. Results: 40 patients with SCAD (95% women, mean age 45±10 years) were included. At least 1 traditional cardiovascular risk factor was present in 40% of patients. Migraine was reported in 43% of patients. Events preceding SCAD included parturition (8%), physical stress (13%), emotional stress (10%) and vasoconstrictor substance-use (8%). 65% of patients had a non-ST elevation ACS (NSTEACS) at presentation, 30% had an ST elevation myocardial infarction (STEMI) and 13% had a cardiac arrest. The left anterior descending artery was most frequently involved (68% of patients), and 13% had involvement of multiple coronary territories. Fibromuscular dysplasia (FMD) was identified in 7 (37%) of 19 patients screened. 68% of patients were managed medically, 30% had percutaneous coronary intervention and 5% had coronary artery bypass grafting. Over a median 16-month follow-up period, 8% of patients had at least 1 recurrent SCAD event. There were no deaths. Conclusions: Patients with SCAD in this study often had multiple coronary territories involved (13%) and extracardiac vascular abnormalities, suggesting a systemic vascular process, which may explain the high incidence of migraine. All patients with SCAD should be screened for FMD and followed closely due to the possibility of recurrence.